Pengaruh Kualitas Pelayanan Publik dan Disiplin Kerja Pegawai Terhadap Kepuasan Masyarakat di Kantor Kecamatan Klari Kabupaten Karawang - Nurul fadilah; N.Neni Triana; Thomas Nedeak (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to analyze the influence of the quality of public services and employee work discipline on community satisfaction at the Klari District Office. The descriptive quantitative method was used in this research with data collection methods using questionnaires and ordinal scales. The population is the people of Klari District, the sample size reached 98 respondents. Data were analyzed using multiple linear regression analysis and referring to a significance level of 0.05. The overall analysis was calculated using the SPSS program. The examiner's results show that (1) partially, the quality of public services has a significant effect on Klari community satisfaction. (2) Partially, employee work discipline has a significant influence on Klari District community satisfaction. (3) Simultaneously, both variables have an influence on Community satisfaction means that the quality of public services and employee work discipline have a significant effect on community satisfaction.